1992
DOI: 10.1523/jneurosci.12-10-03828.1992
|View full text |Cite
|
Sign up to set email alerts
|

A time course for the focal elevation of synthesis of basic fibroblast growth factor and one of its high-affinity receptors (flg) following a localized cortical brain injury

Abstract: Traumatic injury to the CNS initiates transient and unsuccessful regeneration of damaged neural pathways, accompanied by reactive gliosis, angiogenesis, and deposition of a dense fibrous glial/meningeal scar at the wound site. Basic fibroblast growth factor (basic FGF) is a CNS protein with potent effects on neurons, glia, fibroblasts, and vascular endothelial cells. Hybridization and immunocytochemical methods were used to examine temporal and spatial changes in distribution and levels of basic FGF protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(157 citation statements)
references
References 34 publications
10
147
0
Order By: Relevance
“…A similar trend has been reported for fibrin gels loaded with VEGF and heparin. [46] The initial bFGF loading amount did not change the release kinetics significantly at the concentrations studied. Since there was an excess of BSA and heparin employed to stabilize the bFGF, the increase in the bFGF content relative to the total protein/heparin added was small and thus a minimal effect on the protein release kinetics was observed.…”
Section: Discussionmentioning
confidence: 82%
“…A similar trend has been reported for fibrin gels loaded with VEGF and heparin. [46] The initial bFGF loading amount did not change the release kinetics significantly at the concentrations studied. Since there was an excess of BSA and heparin employed to stabilize the bFGF, the increase in the bFGF content relative to the total protein/heparin added was small and thus a minimal effect on the protein release kinetics was observed.…”
Section: Discussionmentioning
confidence: 82%
“…In demyelinating lesions such as in multiple sclerosis, high levels of FGF-2 are produced by reactive astrocytes and macrophages (GomezPinilla et al, 1992;Hinks and Franklin, 1999;Messersmith et al, 2000;Holley et al, 2003). Concomitantly, FGFR1, which is normally low or undetectable in adult white matter (Asai et al, 1993), begins to be expressed by glial cells in lesions (Logan et al, 1992). We demonstrated that application of FGF-2 to mature OLs in culture gives rise to a novel OL phenotype characterized by a downregulation of major myelin-specific proteins and loss of myelin-like membranes, increases in process length, and cell cycle reentry with no mitogenic activity (for review, see .…”
Section: Fgf-2 and Ol/myelin Pathologymentioning
confidence: 99%
“…Could the functional diversity of astroglia, therefore, be secondary to specific localization of these substances? Immunohistochemical reactivity or mRNA expression of several growth factors including bFGF (Ferrara et al, 1988;Finklestein et al, 1988;Gonzalez et al, 1990;Gomez-Pinilla et al, 1992;Logan et al, 1992;Woodward et al, 1992), NGF (Furukawaet al, 1986;Luet al, 1991;Saadet al, 1991;Yoshida and Gage, 199 1;Zafra et al, 1992) EGF Nieto-Sampedro et al, 1988) IGF (Rotwein et al, 1988;Garcia-Estrada et al, 1992) PDGF (Mapstone, 1991;Yeh et al, 199 l), and cytokines such as TGF (Fallon et al, 1990;Wesselingh et al, 1990;Saad et al, 1991) and IL-l (Wesselingh et al, 1990) have been detected in astroglial cells both in vitro and in vivo. None of these studies, however, determined whether there are regional differences in synthesis, expression, or release ofgrowth factors from astroglial cells.…”
Section: Androglia Influence the Number Of Primary Dendritesmentioning
confidence: 99%